Uso de drogas entre universitários: avaliação de possíveis fatores de risco e de proteção - Ferro, Luiz Roberto Marquezi (2014)
The consumption of licit and illicit drugs has increased considerably around the world. This increase is noticeable in the university population, among the many reasons highlights the easy access to drugs by reaching adulthood, the necessity of being accepted into the group, environmental influences, the excessive consumption of alcohol in festive events, without forgetting the power that media has on young people. Based on this, this work becomes important to understand risk factors and protective factors to think about prevention strategies and healthy promotion. This study aimed to identify the abuse of alcohol and other drugs in a sample of college students and their possible association with risk factors (depressive symptomatology, violence and impulsivity) and protective (resilience) presents in life. The methodology used was quantitative research with a population of 152 students of a university in the state of São Paulo, the data collection was online, with a platform creation on the server Survey Monkey, where the IC was insert, and social demographic survey, instruments for measuring risk factors: impulsivity (BIS -11), depression (WHO - 5) and violence (Questionnaire Violence Indicators of II LENAD); and protective factor: resilience (Scale Wagnild and Young). To verify the association between drug abuse and the variables studied were used the logistic regression model, with crude odds ratios (response variable crossed with a explanatory variable) and odds ratios adjusted for all the explanatory variables. The significance level considered was of p < 0.05, with confidence interval (CI) of 95 % for all statistical tests applied. The statistical analyses were conducted by the Statistical Package SAS ® PROC LOGISTIC software 9.0. There was a high alcohol consumption among the assessed students, followed by tobacco and marijuana. The use of other illicit drugs was also significant, with percentages above the general population average. The adjusted logistic regression revealed significant associations between tobacco consumption and religion variables, depressive symptoms, impulsivity and resilience. For the consumption of other drugs (excluding alcohol and tobacco) observed significant associations among the variables religion, violence and depressive symptoms. The study results showed the influence of risk factors for drug use and the importance of protective factors for the prevention of drug abuse. Keywords : Health promotion, university , licit and illicit drugs